2021
DOI: 10.18203/2320-6012.ijrms20212228
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of epithelial ovarian tumors with special reference to human epidermal growth factor receptor-2/NEU and CA-125 expression

Abstract: Background: Ovarian cancer is the second most common gynecologic malignancy. The aim of the study was to evaluate the tissue expression of HER-2/NEU and CA-125 in various epithelial ovarian carcinoma and assess the prognostic significance.Methods: A retrospective study was done in 76 cases of ovarian tumor. IHC was done in 16 cases of epithelial ovarian cancer with HER-2/NEU and CA-125.Results: Total number of cases were 76. Out of these 76 cases, 22 cases were malignant. 16 cases were malignant epithelial ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Barbhuiya et al (2021) [11] found that, out of 76 cases in their study, 22 (28.9%) were malignant. Mukhiya et al (2021) [12] in their study found that out of 157 ovarian neoplasms, 63.06%, 33.76%, and 3.18% of neoplasms were benign, malignant, and borderline, respectively.…”
Section: Singh Et Al (2017)mentioning
confidence: 82%
“…Similarly, Barbhuiya et al (2021) [11] found that, out of 76 cases in their study, 22 (28.9%) were malignant. Mukhiya et al (2021) [12] in their study found that out of 157 ovarian neoplasms, 63.06%, 33.76%, and 3.18% of neoplasms were benign, malignant, and borderline, respectively.…”
Section: Singh Et Al (2017)mentioning
confidence: 82%